Organizational commitment of Vocational College Teachers in Malaysia - Mustafa, Mohamad Zaid; Nordin, Mohd Norazmi; Abdul Razzaq, Abdul Rasid; Ibrahim, Badaruddin (2020)
This study aimed to validate factors related to organizational commitment among teachers in vocational colleges in Malaysia. As we know, the commitment given to the organization will make the organization manageable. However, there are issues regarding the commitment given by the teachers in vocational colleges, which has led to poor performance of college organizations. Some studies have found that factors such as narrative commitment, affective commitment and ongoing commitment cause the overall commitment to the organization to be disrupted. In this study, a fully quantitative approach is used to determine factors in the organization commitment of vocational college teachers. The questionnaire was administered to 264 vocational college teachers in three states in Malaysia namely Negeri Sembilan, Melaka and Johor. The data obtained were then analyzed using Structural Equation Modeling (SEM) using AMOS 21 application. Confirmatory Factor Analysis was performed to obtain factor loading for each element obtained namely narrative commitment, affective commitment and continuous commitment. The analysis results show that the factors reflect the appropriate fit and meet all the criteria for validation. Therefore, the findings of this study can further confirm previous findings on this issue.